The evaluation of workers satisfaction on usability of manual handling equipment among warehouse workers in Malaysia - Abdul Rahman, Ismail; Azis, Noorul Azreen; Mahmood, Salwa; Mohd Rohani, Jafri; Zaidi, Nor Amira Farhana; Mohd Sukri, Suhaimi; Mohd Zain, Mohd Arif Afzan (2022)
Numerous researchers have found that heavy physical demand and improper posture when performing the tasks in various sectors such as manufacturing and warehouse might contribute to the musculoskeletal disorders (MSDs) especially when the tasks involving lifting, pushing and pulling activities. In order to reduce high risk manual handling activities, effectives and usable manual handling equipment (MHE) should be introduce to lower the physical demand of manual material handling (MMH) activities. However, most of the MHE studies previously is not really focus on usability evaluation. So, this study intends to evaluate the usability of current MHE used in manufacturing warehouse operation in term of efficiency, comfortability, energy expenditure, safety aspect, design, productivity, effectiveness and user friendliness. A usability survey was conducted among warehouse workers in manufacturing company at southern region of peninsular Malaysia. Besides that, the prevalence of backpain among the warehouse workers was measured through Modified Nordic Discomfort Assessment tools that are incorporate in the usability survey. Result for the most least agreement in user usability for pallet jack was energy expenditure (3.73), efficiency (3.96) and comfortability (3.99); for load carrying cart was energy expenditure (3.62), design (3.74) and comfortability (3.90); for forklift was comfortability (3.87), design (3.93) and safety (4.08); for pallet stackers was energy expenditure (3.79), design (3.82) and user friendliness (3.82); for conveyor system was productivity (3.50), comfortability (4.00) and safety (4.00). It was also found that the highest prevalence of MSDs among warehouse workers was lower back, followed by legs (left and right) and shoulders (left and right). In conclusion, most MHE available in manufacturing warehouse operation lacking in term of energy expenditure, efficiency, comfortability, design and user friendliness. It is clear that the first stage in design criteria for MHE should be developing an understanding of the user usability requirement to ensure the aids are suitable for the tasks.